Effect of whole-body vibration combined with an exercise program in females with chondromalacia: A randomized controlled trial - Anwar Abdelgayed Ebid; Ali A. Elmonsif Thabet; Kadrya H Battecha; Abeer R Ibrahim; Hayam Mahmoud; Mohamed Mohamed Ibrahim Salem; Revan Salem Alammari; Farah Obaid Almuqati; Ghada Jameel Thiga; Maria Ahmad Alsaedi; Leen Khalid Bahamdain (Sport TK)
The aim of this study was to assess the influence of whole-body vibration (WBV) training combined with an exercise program on both pain and quadriceps isometric muscle force in adult females with chondromalacia patellae (CMP). This study employed a randomized controlled design with 40 healthy older female volunteers. Participants were divided into two groups: 20 in the whole-body vibration (WBV) group and 20 in the exercise (EX) group. The WBV group underwent a 4-week WBV training program, 3 times a week, alongside exercise, while the EX group participated in a 4-week exercise program without WBV. Primary outcomes, assessed at baseline and after 4 weeks, included pain intensity measured using a visual analogue scale (VAS) and quadriceps isometric muscle force measured by a Hand Held Dynamometer. The WBV training group exhibited significantly greater enhancements than the EX-group in terms of mean values and percentage changes in pain intensity and quadriceps isometric muscle force. The addition of WBV to exercise yields significantly superior outcomes compared to exercise training alone in CMP. The observed disparities between the WBV training group and the EX-group underscore the efficacy of WBV as a potent physical therapy intervention for the rehabilitation of CMP patients, particularly in enhancing strength gains and decreasing pain.